Rehabilitación mediante fisioterapia para pacientes caninos con síndrome neuropático tratados en la Universidad de las Américas - Bodero Gavilanes, Dayana del Rocío (2011)
Neuropathic syndrome or peripheral neuropathy is a group of disorders, which cover a wide range of conditions that comprise the peripheral nervous system (roots, ganglia, plexuses and nerve fibers), mainly affecting myelin, axon, or a combination of both , using conventional treatments such as physical rehabilitation or physical therapy, which help control pain without the use of drugs. Physical therapy has a beneficial role on the soft tissues, joints and bones, taking into account that after trauma is important to the recovery of vascularization and tissue reorganization to prevent fibrosis, and avoiding a reduction in capacity. To begin physical therapy is necessary to have knowledge and assess the patient determine their condition, thanks to the implementation of Zookinesico diagnosis, which includes a physical examination, neurological examination and orthopedic examination, the assessment of passive range of motion (PROM)movement of the affected area.